PROCESS ANALYSIS AND IMPROVEMENT IN QUALITY MANAGEMENT SYSTEMS (A CASE STUDY IN AN ALUMINUM PRODUCTION COMPANY) (Ustozlar uchun, 2026)
Today, the ability of enterprises operating in the manufacturing sector to achieve sustainable competitive advantage is directly related not only to production capacity but also to the degree of effectiveness with which they implement quality management systems. Rising customer expectations, intensified global competition, and technological developments have directed enterprises toward more systematic, traceable, and continuously improvable management models. In this regard, the Quality Management System (QMS) has become a strategic management approach for standardizing processes, reducing error rates, increasing customer satisfaction, and improving operational efficiency.